Formação de vocações adultas. Questões em torno do processo formativo convencional - Nentwig, Roberto (Revista Eclesiástica Brasileira, 2019)
Este artigo trata de algumas questões relativas ao processo tradicional de formação presbiteral. Diante do contexto de mudança de época, questiona-se a capacidade de os seminários tradicionais atenderem a demanda dos candidatos que se apresentam para o ingresso. Considera-se ainda que existam fatores de imaturidade na nova geração: os jovens de hoje são ainda adolescentes ao longo do processo formativo. Por isso, surge o questionamento sobre a viabilidade de novas estruturas formativas. Como luzes, apresentamos as características de institutos de formação de vocações adultas, que acolhem homens já mais amadurecidos e que tem estabilidade e emprego fixo. O artigo apresenta o relato de dois institutos de formação de adultos: Bovendonk, na Holanda, e o Instituto Discípulos de Emaús (IDE), no Brasil. Abstract: This article refers to some matters as they are related to the traditional presbyteral formation. As we stand before the context of times changing, the capacity of related-traditional seminaries is questioned – for their reality of meeting the demand of candidates who identify themselves for such intake. Still-existing factors of immaturity within the new generation – as shown – are considered upon: as today’s youth is still under a teenage-reality for along the process of their formation. Therefore, a new questioning over the practicability of new forming structures arises. As in a burst of a new enlightenment, we introduce the characteristics of institutes of adults’ vocations, meaning ‘men of greater maturity’ who present personal stability and a steady occupation as a means of work. The article presents the description of two formation institutes of adults: Bonvendonc, and the Instituto Discípulos de Emaús (IDE), in Brazil. Keywords: Formation; Maturity; Seminary; Adult vocations.